Optimizing risk stratification in pediatric febrile urinary tract infection: A single-center study in Japan - Tomohiro Inoguchi; Riku Hamada; Yooka Nam; Chikako Terano; Ryoko Harada; Satoshi Narumi; Yuko Hamasaki; Kenji Ishikura; Masataka Honda; Hiroshi Hataya (PLoS ONE, 2025)
Selecting optimal therapeutic interventions for febrile urinary tract infection (f-UTI) is crucial to prevent complications such as kidney scarring. While current clinical guidelines provide risk-stratified imaging recommendations, they are largely based on Western populations and lack specific predictors for which children will ultimately require therapeutic interventions. This study aimed to establish risk stratification criteria for East Asian children with first-episode f-UTI. This retrospective single-center study analyzed patients aged 2–24 months with first-episode f-UTI. All patients underwent a standardized diagnostic and management protocol, including kidney–bladder ultrasound (KBUS) and voiding cystourethrography (VCUG), to ensure uniform evaluation. The primary outcome was “requirement for therapeutic intervention,” defined as one or more of the following: (1) urological surgery (2) antimicrobial prophylaxis (for vesicoureteral reflux grade ≥III) and (3) antimicrobial treatment for recurrent f-UTI. Multivariate logistic regression was performed to identify independent predictors associated with the interventions. A total of 216 patients were included (median age: 4 months). Overall, 59 patients required therapeutic interventions. Non- Escherichia coli infection (OR 3.3, 95% CI 1.3–8.7) and abnormal KBUS findings (OR 5.3, 95% CI 2.7–10.6) were identified as independent predictors. The sensitivity and specificity of the factors for predicting therapeutic intervention were 64.4% and 73.2%, respectively. This study identified non- E. coli infection and abnormal KBUS findings as key predictors for therapeutic interventions in East Asian children with first-episode f-UTI. These findings suggest that a more targeted approach based on these factors may optimize risk stratification and patient selection for VCUG, improving clinical decision-making.